Molecular typing and antimicrobial resistance profiling of 33 mastitis-related Staphylococcus aureus isolates from cows in the Comarca Lagunera region of Mexico - Y. Mora-Hernández (Nature Portfolio, 2021)
Abstract Mastitis in cows is a major cause of economic losses and it is commonly associated with Staphylococcus aureus. Little is known about the S. aureus lineages causing mastitis in Mexican cattle. The aim of this study was to type S. aureus isolates causing mastitis in cows from the Comarca Lagunera region in Mexico in 2015–2016. Multi-locus variable number tandem repeat fingerprinting (MLVF) of 33 S. aureus isolates obtained from 210 milk samples revealed the MLVF clusters A (n = 1), B (n = 26), C (n = 5) and D (n = 1). Spa-typing showed that clusters A and B represent the spa-type t224, cluster C includes spa-types t3196 and t416, and cluster D represents spa-type t114. The different spa-types were mirrored by the masses of protein A bands as detected by Western blotting. Antimicrobial susceptibility testing showed that one isolate was susceptible to all antimicrobials tested, whereas all other strains were resistant only to benzylpenicillin. These findings show that only four S. aureus lineages, susceptible to most antimicrobials, were responsible for causing mastitis at the time of sampling. Lastly, many isolates carried the same small plasmid, designated pSAM1. The high prevalence of pSAM1 amongst the antimicrobial-susceptible isolates suggests an association with bovine colonization or mastitis rather than antimicrobial resistance.